Tuberculosis in malaysia: Predictors of treatment outcomes in a national registry - Harmy, Mohamed Yusoff; Su May, Liew; Ee Ming, Khoo (2015)
OBJECTIVES To determine treatment outcomes and associated predictors of all patients registered in 2012 with the Malaysian National Tuberculosis (TB) Surveillance Registry. METHODS Sociodemographic and clinical data were analysed. Unfavourable outcomes included treatment failure, transferred out and lost to follow-up, treatment defaulters, those not evaluated and all-cause mortality. RESULTS In total, 21 582 patients were registered. The mean age was 42.36 ± 17.77 years, and 14.2% were non-Malaysians. The majority were new cases (93.6%). One fifth (21.5%) had unfavourable outcomes; of these, 46% died, 49% transferred out or defaulted and 1% failed treatment. Predictors of unfavourable outcomes were older age, male sex, foreign citizenship, lower education, no bacille Calmette-Guérin (BCG) vaccination scar, treatment in tertiary settings, smoking, previous anti-tuberculosis treatment, human immunodeficiency virus infection, not receiving directly observed treatment, advanced chest radiography findings, multidrug-resistant TB (MDR-TB) and extra-pulmonary TB. For all-cause mortality, predictors were similar except for rural dwelling and nationality (higher mortality among locals). Absence of BCG scar, previous treatment for TB and MDR-TB were not found to be predictors of all-cause mortality. Indigenous populations in East Malaysia had lower rates of unfavourable treatment outcomes. CONCLUSIONS One fifth of TB patients had unfavourable outcomes. Intervention strategies should target those at increased risk of unfavourable outcomes and all-cause mortality.